Pengaruh Kebijakan Hutang Dan Kebijakan Dividen Terhadap Nilai Perusahaan (Perusahaan Makanan Dan Minuman Tahun 2017-2021) - Andini Fajriani; Immas Nurhayati; Renea Shinta Aminda (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to provide empirical evidence regarding debt policy and dividend policy in predicting company value by testing each variable. The data used are secondary data and the method used is regression analysis of panel data with the help of the Eviews 12 program to obtain a comprehensive picture of the relationship between one variable and another. The method used in the selection of objects in this study is purposive sampling involving 10 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2021 with an observation period of 5 (five) years of 50 company samples.The results of this study are that debt policy (DER) using the PER formula does not have a partially significant effect. And the debt policy (DER) using the PBV formula has a partially significant effect. Meanwhile, the dividend policy (DPR) using the PER formula has a partially significant effect. And the dividend policy (DPR) using the PBV formula does not have a partially significant effect. The results of the simultaneous regression analysis show that the debt policy (DER) and dividend policy (DPR) using the PER and PBV formulas simultaneously affect firm value.